Deteksi Kecurangan Laporan Keuangan dengan Pendekatan Vousinas Fraud Hexagon Model pada Perusahaan Sektor Energi di Indonesia - Fivit Apriliya; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of the fraud hexagon model by involving elements of stimulus, capability, opportunity, rationalization, ego/arrogance, and collusion to detect financial statement fraud. The sample of this study is energy sector companies listed on the Indonesia Stock Exchange in 2021-2023, totaling 41 companies or 123 data points determined using the purposive sampling method. Hypothesis testing in this study used logistic regression analysis. The results of this study indicate that stimulus elements in terms of financial stability and collusion affect financial statement fraud. Other elements are stimulus elements in terms of external pressure, financial targets, and personal financial need; capability elements; opportunity elements regarding ineffective monitoring and nature of industry; rationalization elements; and ego/arrogance elements that do not affect financial statement fraud. This research is expected to provide information on the factors that cause fraud and detect fraud in financial reports. It can be used as a reference to improve the auditor's duties in testing the fairness and appropriateness of the presentation of financial reports.